1973
DOI: 10.1246/bcsj.46.152
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of Crystalline Rare Earth Carbonates

Abstract: The factors which influence the crystallization of rare earth carbonates were studied. Crystalline rare earth carbonates were precipitated at various temperatures from aqueous solutions by using sodium carbonate, sodium bicarbonate, trichloroacetic acid, and urea as precipitants. The crystal parameters, compositions, and factors concerning the formations of various carbonates, such as lanthanite-type Ln2(CO3)3·8H2O(Ln=La, Ce), tengeritetype Ln2(CO3)3·nH2O(Ln=Nd, Sm, Gd, Dy, Ho, Er, and Y, n=2–3), monoxocarbona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

1973
1973
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 5 publications
5
30
0
Order By: Relevance
“…However, their particle shapes are reported to be irregular. The factors that influence the crystallization of rare-earth carbonates have been reported by Nagashima et al [26].…”
Section: Introductionmentioning
confidence: 86%
“…However, their particle shapes are reported to be irregular. The factors that influence the crystallization of rare-earth carbonates have been reported by Nagashima et al [26].…”
Section: Introductionmentioning
confidence: 86%
“…Tanaka et al (2004) showed that the partition coefficients of La, Ce and Pr using lower REE concentration solutions (e.g., 1 ppb) are smaller than those of the higher REE concentrations (10 to 100 ppb), but HREE partition coefficients for low and high concentration cases are similar. They pointed out that these observations might be related to the difference between light and heavy REE in the syntheses of crystalline REE carbonates reported in Nagashima et al (1973) A-2 Shannon (1976).…”
Section: Table 4 the Growth Rates Of Calcite Crystals In This Study mentioning
confidence: 99%
“…Alternatively the light REEs may have precipitated partly as REE carbonate like REE 2 (CO 3 ) 3 , not as NaREE(CO 3 ) 2 . Nagashima et al (1973) reported the synthesis of crystalline REE carbonates from REECl 3 solutions by addition of NaHCO 3 or Na 2 CO 3 : At 20°C and 1 atm, lanthanite-type carbonates [REE 2 (CO 3 ) 3 ·8H 2 O] precipitated in the La and Ce solutions, whereas NaREE(CO 3 ) 2 ·nH 2 O precipitated in the other REE solutions. From the plots of Fig.…”
Section: Comparison Between Laboratory and Field Datamentioning
confidence: 99%